2013
DOI: 10.1590/0103-6440201302051
|View full text |Cite
|
Sign up to set email alerts
|

Similar Sealability Between Bioceramic Putty Ready-To-Use Repair Cement and White MTA

Abstract: This study was designed to assess the ability to prevent glucose penetration of a bioceramic putty ready-to-use repair cement comparing to white mineral trioxide aggregate (WMTA). After root canal instrumentation, the apical 3 mm of maxillary incisors were resected and root-end cavities with depth of 3 mm were prepared with ultrasound and filled with the tested materials (15 roots per group). All roots were mounted in a double chamber system to assess glucose penetration using 15 psi pressure application. Afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 24 publications
0
28
0
1
Order By: Relevance
“…Nanosized biomaterials play an important role in tissue repair and regeneration due to their unique nanostructure and biological functions. Recently, as a revolutionary ready-to-use nanoparticulate bioceramic with the advantage of handling ease, iRoot BP Plus has been developed for potential dental surgery applications [13,15]. Our results first showed that nanoparticulate iRoot BP Plus possessed excellent apatite-forming ability, promoted in vitro recruitment of DPSCs, and facilitated the dentin bridge formation in a pulp repair model in vivo.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Nanosized biomaterials play an important role in tissue repair and regeneration due to their unique nanostructure and biological functions. Recently, as a revolutionary ready-to-use nanoparticulate bioceramic with the advantage of handling ease, iRoot BP Plus has been developed for potential dental surgery applications [13,15]. Our results first showed that nanoparticulate iRoot BP Plus possessed excellent apatite-forming ability, promoted in vitro recruitment of DPSCs, and facilitated the dentin bridge formation in a pulp repair model in vivo.…”
Section: Discussionmentioning
confidence: 72%
“…iRoot BP Plus is a novel ready-to-use laboratory-synthesized calcium silicate-based nanoparticulate bioceramic paste, which has been claimed to offer revolutionary improved performance compared with current hand-mixed MTA. iRoot BP Plus is an insoluble, radiopaque, aluminium-free and zirconium oxide-incorporated material developed for potential dental surgery applications [13,14]. Because of its nanomodified nature and ease of handling, iRoot BP Plus has been speculated to be a promising MTA alternative.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maxillary segment of the syringe containing the glucose solution is connected to a pressure source to create a headspace pressure of 103 kPa per 60 minutes (76). Souza et al (79) amplified the pressure in the maxillary chamber of the GLM system to accelerate glucose leakage from weeks to hours in order to decrease the risk of bacterial growth and long-term water evaporation, while maintaining the capacity to detect the leaking samples.…”
Section: Resultsmentioning
confidence: 99%
“…MTA-based root-end filling materials have been developed (4,5). An experimental sealer (MTA Sealer) was developed based on white Portland cement, zirconium oxide (radiopaque filler), calcium chloride (additive) and resin to be used as a root canal filling material (5).…”
Section: Introductionmentioning
confidence: 99%